The productivity effects of bank mergers: Evidence from the UK building societies - Haynes, Michelle; Thompson, Steve (Journal of Banking & Finance, 1999)
This paper presents an empirical investigation of the impact of acquisition activity on financial intermediary productivity. Specifically, it uses an augmented production function approach to investigate the impact of acquisition, after controls for input changes. The model is estimated on an unbalanced panel of 93 UK building societies over the period 1981–1993, using data on their core financial intermediation activities which, it is suggested are particularly appropriate for our purposes. In contrast to much of the existing merger literature, which for the most part uses financial performance data, our results DO indicate significant and substantial productivity gains following acquisition. These are consistent with an acquisitions process in which less efficient firms are acquired and reorganized. The post-merger gains appear to increase substantially in the post-deregulation period, when pressures to minimize cost are widely considered to have increased.